Prognostic Potential of Heart Rate and Hypertension in Multiple Myeloma Patients - Wang, Jie; Tang, Manyun; Long, Yunxiang; Song, Jingzhuo; Chen, Limei; Wang, Mengchang; Li, Yongxin; Sun, Chaofeng; Yan, Yang (Frontiers in Cardiovascular Medicine, 2021)
Background: The prognosis of patients with multiple myeloma (MM) is variable and partly depends on their cardiovascular status. The presence of arrhythmias can lead to worse outcomes. Therefore, this study aimed to evaluate the potential of heart rate (HR) and hypertension in predicating the outcomes of MM patients. Methods: This study retrospectively enrolled patients with MM between January 1, 2010, and December 31, 2018, at the First Affiliated Hospital of Xi'an Jiaotong University. The endpoint was all-cause mortality. The Pearson's chi-square test was used to assess the association between hypertension and outcomes. Univariate and multivariate Cox proportional hazards models were developed to evaluate the relationship between HR and all-cause mortality. Results: A total of 386 patients were included. The mean HR was 83.8 ± 23.1 beats per minute (bpm). Patients with HR >100 bpm had a higher all-cause mortality (79.4%, 50/63) than those with 60 ≤ HR ≤ 100 bpm (39.9%, 110/276) and <60 bpm (19.1%, 9/47) (p < 0.001). Subgroup analysis based on the International Staging System and sex revealed similar relationships (p < 0.01). When stratified by age, patients with HR >100 bpm had higher all-cause mortality than those with a lower HR when age was <65 years or 65–75 years (p < 0.001) but not >75 years. The proportion of patients with hypertension was 54.7% (211/386). However, hypertension was not associated with all-cause mortality in MM patients (χ2=1.729, p > 0.05). MM patients with HR >100 bpm had the highest all-cause mortality. Conclusions: The prognostic potential of HR may be useful in aiding risk stratification and promoting the management of these patients.